2016
DOI: 10.2147/opth.s107726
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a preloaded intraocular lens delivery system on operating room efficiency in routine cataract surgery

Abstract: PurposeThe aim of this study was to evaluate the operational impact of using preloaded intraocular lens (IOL) delivery systems compared with manually loaded IOL delivery processes during routine cataract surgeries.MethodsTime and motion data, staff and surgery schedules, and cost accounting reports were collected across three sites located in the US, France, and Canada. Time and motion data were collected for manually loaded IOL processes and preloaded IOL delivery systems over four surgery days. Staff and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 12 publications
0
32
1
2
Order By: Relevance
“…To provide better operating conditions, the P-IOL delivery systems were developed. The perceived bene ts of P-IOL delivery systems include the elimination of IOL injector loading variability, avoidance of potential IOL loading errors, lower risk for instrument contamination and reduced operation time [10,11,[13][14][15]. In this study, our data showed that in a 1-OR scenario, application of P-IOL system reduced average total case time by 1.3 min (-7.7%) relative to M-IOL system.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…To provide better operating conditions, the P-IOL delivery systems were developed. The perceived bene ts of P-IOL delivery systems include the elimination of IOL injector loading variability, avoidance of potential IOL loading errors, lower risk for instrument contamination and reduced operation time [10,11,[13][14][15]. In this study, our data showed that in a 1-OR scenario, application of P-IOL system reduced average total case time by 1.3 min (-7.7%) relative to M-IOL system.…”
Section: Discussionmentioning
confidence: 64%
“…Time and motion data were collected over a total of 12 surgery days as described previously [11]. The time of the procedures was recorded using a stopwatch.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…High refractive indeks, high Abbe value, glistening free and aspheric optical design upgrade the image quality [26][27][28] . Preloaded cartridge is very important factor that reduces peroperative and postoperative complication rates [18] .…”
Section: Resultsmentioning
confidence: 99%
“…The use of the preloaded cartridge spreads more and more. Preloaded cartridge shortens the duration of surgery, reduces the lens contamination and deformation [18] . It can be expected the use of manual cartridge going to vanish in the coming years.…”
Section: çAğrı İlhanmentioning
confidence: 99%